2007
DOI: 10.1088/0031-9155/52/17/017
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of individual evoked potential components using iterative independent component analysis

Abstract: Independent component analysis (ICA) has been successfully employed in the study of single-trial evoked potentials (EPs). In this paper, we present an iterative temporal ICA methodology that processes multielectrode single-trial EPs, one channel at a time, in contrast to most existing methodologies which are spatial and analyze EPs from all recording channels simultaneously. The proposed algorithm aims at enhancing individual components in an EP waveform in each single trial, and relies on a dynamic template t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…Contrary to all other methods, we have proposed an alternative methodology [42,43] that can extract individual components out of the complete EP waveform. The method analyzes single-trial EPs based on independent component analysis (ICA) and relies on the hypothesis that brain activity resulting from an experimental stimulus is independent from neurophysiological artifacts and background activity [32,44,45].…”
Section: Ep Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to all other methods, we have proposed an alternative methodology [42,43] that can extract individual components out of the complete EP waveform. The method analyzes single-trial EPs based on independent component analysis (ICA) and relies on the hypothesis that brain activity resulting from an experimental stimulus is independent from neurophysiological artifacts and background activity [32,44,45].…”
Section: Ep Estimationmentioning
confidence: 99%
“…In particular, we compared [46] the iterative ICA (iICA)-based single-trial analysis against traditional ensemble averaging using synthetic and real data from normal subjects and found that the iICA method provides improved estimates of the N100 component. We also showed that these findings are independent of the model assumed for EP generation and remain true for both the phase-resetting and additive models.…”
Section: Ep Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate different SNR conditions, two groups of 50 synthetic sweeps were generated. The first group comprised sweeps having a SNR uniformly distributed in the interval [0.2-0.4], while the second one presented SNR levels in the interval [1-1.2]; a similar procedure can be found in several works (e.g., Iyer and Zouridakis, 2007;Zouridakis et al, 2007). For instance, in the simulated dataset where the SNR varied uniformly between 0.2 and 0.4, the average power of the noise was from 2.5 to 5 times greater than the power of the useful signal.…”
Section: Synthetic Datamentioning
confidence: 99%
“…In the present study, we follow a different approach that is based on our recent work [4,15] with independent component analysis (ICA) of single trial EPs. The method developed, termed iterative ICA (iICA), is an iterative implementation of the information maximization algorithm originally proposed by Makeig et al [6].…”
Section: Introductionmentioning
confidence: 99%